Studies towards the synthesis of lindenene: Unexpected stereochemical outcome of an intramolecular cyclopropanation reaction and synthesis of (+/-)-epi-Lindenene and (+/-)-iso-Lindenene - Fenlon, T; Schwaebisch, D; Mayweg, A; Lee, V; Adlington, R; Baldwin, J (2007)
Investigation towards the synthesis of the furanosesquiterpene Lindenene using an intramolecular cyclopropanation reaction gave unexpected ring-junction isomerisation products. These products were elaborated to (±)-epi- lindenene and (±)-iso-lindenene. © Georg Thieme Verlag Stuttgart.